Perilaku Hewan: Respon Gerak Renang Ikan Nila (Oreochromis niloticus L) terhadap Limbah Cair Industri Kain Jumputan - Nurhaliza Agustria; Susy Amizera; Didi Jaya Santri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the differences in swimming behavior of Nile tilapia (Oreochromis niloticus L) exposed to batik dye industrial wastewater and to identify its effects on fish swimming patterns. The method used was a qualitative approach with experimental observation. The swimming behavior of Nile tilapia was observed in wastewater and control water conditions for 5 minutes, with four repetitions. Water quality parameters, including pH, TDS, TSS, and DO, were also analyzed. The results showed that the wastewater quality did not meet the regulatory standards, with TSS and TDS exceeding the limits and DO below the standard threshold, while pH was within the acceptable range. The swimming patterns of Nile tilapia in wastewater conditions were characterized by higher activity and irregular movements compared to control conditions. In conclusion, batik dye industrial wastewater significantly affects the swimming behavior of Nile tilapia, leading to increased activity and irregular movements. Keywords: Swimming Behavior, Nile Tilapia, Batik Dye Wastewater